Vivienda colectiva La Carolina - Swoboda Jaramillo, Otto Sebastián (2020)
The hyper center of Quito presents several problems in terms of morphology, demography, mobility, green areas, among others. Due to this, the following work is presented, initially carrying out an urban approach that seeks to provide different urban solutions to improve the quality of life in the sector. For this reason, there are seven clusters or centralities within the study area with specific vocations and equipment that responds to the site and the environment. In addition to this, the clusters seek to densify the city and avoid the predominance of the dispersed city towards the valleys and mountainsides that adjoin Quito, making new forms of housing become a fundamental axis to be treated within the urban area as it the collective housing, the shared, complementary and transformable spaces that can be given to improve efficiency in an architectural space.